If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -24 = 3(2x + -8) Reorder the terms: -24 + 6x = 3(2x + -8) Reorder the terms: -24 + 6x = 3(-8 + 2x) -24 + 6x = (-8 * 3 + 2x * 3) -24 + 6x = (-24 + 6x) Add '24' to each side of the equation. -24 + 24 + 6x = -24 + 24 + 6x Combine like terms: -24 + 24 = 0 0 + 6x = -24 + 24 + 6x 6x = -24 + 24 + 6x Combine like terms: -24 + 24 = 0 6x = 0 + 6x 6x = 6x Add '-6x' to each side of the equation. 6x + -6x = 6x + -6x Combine like terms: 6x + -6x = 0 0 = 6x + -6x Combine like terms: 6x + -6x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| (7^1/8)/(-2) | | -2u-12=-8u-18 | | 1.2y+5=-2.8y-3 | | -39=n-11 | | 3x(x+2)+4=5x+7 | | 2v-1=-(-2v+1) | | 15=-3+x | | .889=16 | | 2x-7x=-8-27 | | 6v+9=-8v-19 | | 8x-40=6x-8 | | x-5+17=15 | | 7x+4=10x-11 | | (5/4)(-3/10) | | Y+4=-4y+4 | | -6=x-9 | | -3-2(-8y+1)=2(9y+4)-2 | | .12(y-7)+.14y=.16y-.07(10) | | 3(4x-2)=3*4+6 | | -6=r+2 | | (2X/5)+X=70 | | .26p=.104 | | -5x-10y=20 | | -3c-9+24= | | z=m-y | | 8a+5b=-3 | | 10w-3=w+5 | | -3c+9+24= | | .50x-3=12 | | -5(7+8x)-7x=-35+2x | | 4x-8-7x-3= | | -47.04=-11.2x |